Iliac crest trabecular bone mass and structure in patients with non-steroid treated rheumatoid arthritis. - Mellish, R W (1987)
Iliac crest trabecular bone volume and structure have been studied in bone biopsy specimens from 48 patients with classical or definite rheumatoid arthritis, none of whom had received steroids. Results were compared with those obtained from healthy controls matched for age and sex. The mean trabecular bone volume in female patients aged 34-50 years was significantly lower than in controls (p less than 0.01); in male patients aged 34-50 years values were also lower than those in controls (mean (SD) 17.8 (3.2) v 22.4 (5.6)% total medullary volume), though this difference was not statistically significant. Values in older patients were similar to those of controls. The mean trabecular plate thickness was significantly lower in female patients in all three age groups when compared with the controls (p less than 0.005, 0.05, and 0.005). Similar but non-significant changes were seen in male patients. The mean trabecular plate density, an index of trabecular number, and the mean trabecular plate separation showed no age related change in either male or female patients, in contrast with the female control group, in whom the mean trabecular plate density decreased and separation increased with age. These results suggest that non-steroid treated rheumatoid arthritis is associated with premature bone loss, the structural basis of which is trabecular thinning.